Assessment of Glomerular Filtration Rates by Cockcroft-Gault and Modification of Diet in Renal Disease Equations in a Cohort of Omani Patients - Al-Osali, Magdi E. (Sultan Qaboos University Medical Journal, College of Medicine & Health Sciences, 2014)
OBJECTIVES: Glomerular filtration rate (GFR) is the best index of renal function and is frequently assessed by corrected creatinine clearance (CCL(cr)). The limitations of CCL(cr) have inspired researchers to derive easy formulas to estimate GFR, with Cockcroft-Gault (C-G) and the modification of diet in renal disease (MDRD) being the most widely used. This study aimed to evaluate the validity of these equations by finding the relation between CCL(cr) and estimated GFR (eGFR) by C-G, modified C-G and MDRD equations. METHODS: From 2007 to 2011, 158 subjects were analysed for serum creatinine and CCL(cr) at Bowsher Polyclinic, Muscat, Oman. The C-G equation was used to obtain eGFR(C-G) which was adjusted to body surface area (BSA) to obtain eGFR(mC-G), and the MDRD equation was used to obtain eGFR(MDRD). The eGFR(MDRD), eGFR(mC-G) and eGFR(C-G) were then compared to CCL(cr). RESULTS: The eGFR(MDRD), eGFR(mC-G) and eGFR(C-G) significantly correlated with CCL(cr), with a slightly stronger correlation with eGFR(MDRD) (r = 0.701, 0.658 and 0.605, respectively). A receiver operating characteristic curve analysis showed that the diagnostic accuracy of eGFR(MDRD) for diagnosing chronic kidney disease (CKD) was higher than that of eGFR(mC-G), which in turn was higher than that of eGFR(C-G) (area under the curve was 0.846, 0.831, and 0.791; cut-off limits were 61.9, 58.3 and 59.5, respectively). CONCLUSION: C-G and MDRD equations can be an alternative to the CCL(cr) test for assessing GFR, thus avoiding the need for the cumbersome and expensive GFR test. The MDRD formula had greater validity than the C-G equation and the C-G equation validity was improved by an adjustment to BSA.